2017
DOI: 10.1177/0018726717711236
|View full text |Cite
|
Sign up to set email alerts
|

The role of co-workers in the production of (homo)sexuality at work: A Foucauldian approach to the sexual identity processes of gay and lesbian employees

Abstract: Adopting a Foucauldian perspective that focuses on the way power contributes to ensuring that sexuality leads a discursive existence, this study investigates the role of co-workers in the production of gay and lesbian employees’ sexuality. Drawing on interviews with 31 employees who self-identify as gay or lesbian, this article makes three contributions to the literature on sexual minorities’ identities at work. First, it shows how the production of sexuality is shaped by relations of attribution, evocation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…On the one hand, as a public organization, it is expected to operate as a ‘representative bureaucracy’ reflecting the diversity of the population and as a role model for the employment of vulnerable individuals (Coleman, Brudney, & Kellough, 1998). On the other, it is subject to increased accountability for the ‘activation’ of the unemployed, as part of a New Public Management discourse emphasizing effectiveness, as reflected in the intensification of work through teams of interchangeable, highly flexible workers (Randle & Hardy, 2017; Zanoni, 2011) and increased co-workers’ gaze (Van Laer, 2018). In this ‘heterogeneous space’, to use Dobusch’s (2017b) term, the construction of disabled employees as the negation of the ideal worker appears to simultaneously cater for both organizational goals.…”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, as a public organization, it is expected to operate as a ‘representative bureaucracy’ reflecting the diversity of the population and as a role model for the employment of vulnerable individuals (Coleman, Brudney, & Kellough, 1998). On the other, it is subject to increased accountability for the ‘activation’ of the unemployed, as part of a New Public Management discourse emphasizing effectiveness, as reflected in the intensification of work through teams of interchangeable, highly flexible workers (Randle & Hardy, 2017; Zanoni, 2011) and increased co-workers’ gaze (Van Laer, 2018). In this ‘heterogeneous space’, to use Dobusch’s (2017b) term, the construction of disabled employees as the negation of the ideal worker appears to simultaneously cater for both organizational goals.…”
Section: Methodsmentioning
confidence: 99%
“…Sanguinity regarding the future of identities studies in MOS has not (at least not yet) translated into consensus on how best to take forward debates on identities, which approaches are likely to prove most generative, what questions are most pressing, or the topics that are least justifiably under-explored. Certainly, there is no shortage of interesting and less studied groups to research, such as those with mental health issues (Elraz, 2017), or newly considered resources for identity work, such as sexuality (Van Laer, 2017) and cosmopolitanism (Skovgaard-Smith & Poulfelt, 2017). Each identities scholar, it appears, has their own favoured concept, approach, perspective, theory, critique or agenda and associated issues, questions, gripes, critiques and recommendations.…”
Section: Looking Forwardmentioning
confidence: 99%
“…Partly drawing on Alvesson and Willmott’s identity regulation framework, a large and still growing strand within the critical diversity literature analyses identity construction along the lines of social minority categories such as gender (Kelan, 2010; Ortlieb and Sieben, 2019), ethnicity (Van Laer and Janssens, 2017; Zanoni et al, 2017), religion (Essers and Benschop, 2009), sexuality (Rumens and Broomfield, 2014; Van Laer, 2018) and dis-/ability (Jammaers and Zanoni, 2020). Furthermore, several studies found that organizational practices aimed at fostering diversity and inclusion such as training and promotion procedures trigger identity work of minority group members (Jammaers and Zanoni, 2020; Villesèche et al, 2018; Yang and Bacouel-Jentjens, 2019; Zanoni and Janssens, 2007).…”
Section: Theorising Inclusion and Identitymentioning
confidence: 99%